Rancang Bangun Prototype Smart Door dengan Sistem Voice Recognition V3 Berbasis Arduino - Okky Hermawanto; Sri Mulyanto Herlambang; Eddi Eddi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Most door accesses used in homes still use conventional keys. Where the use of manual keys is still vulnerable to loss or damage and is not very safe to use, because manual keys can be duplicated or duplicated by other people. This certainly feels less practical and flexible. This research aims to help improve door security. With a voice recognition system, only certain people can access it using a certain access code. Researchers used the trial and error method. The factor being tried is the voice recognition V3 module which can read voice recordings. The results of this research can be implemented in the form of a tool, where the system can open and close house doors according to the planned design, namely through voice commands and the designed system can run normally according to the automatic system that has been designed in prototype form. The conclusion from this research is that the voice recognition module is capable of recording sounds up to a distance of 20 cm. In voice recording < 10 cm the module is relatively easier to receive voice commands, in recording > 10 cm and < 15 cm the module is slightly less able to receive voice commands, so that in voice recording at a distance of 15 cm to 20 cm the module is very poor in receiving commands sound well.